Teaching multicultural motif and craft design focusing on craft activity in secondary school / Mohammed Razmi Abdul Kahar - Abdul Kahar, Mohammed Razmi (2012)
Playing with colors, designs, decorations and ornamental modes can really provide serenity and tranquility. Multicultural design motif, combined with the right technique, can help one to better appreciate culture .The beauty of a multicultural design motif is a result of the mixture of interesting patterns and proper and creative process in combining and adapting existing independentculture- based motifs. When independent motifs from different cultures are combined, multicultural motif is born. In Malaysian secondary schools' art class, the only motif available and taught is the Malay motif. In the spirit of 1 Malaysia, it is considered that multicultural motif also needs to be taught and introduced to students whereby they will have the opportunity to learn more and appreciate other cultures than theirs. The teachings of multicultural motif in art classes can also provide new insights and fresh ideas into craft design and craft decoration. Hence, it is hoped that by having multicultural motif embedded in Malaysian secondary schools' art classes, the government's effort in promoting the 1 Malaysia campaign will have more ground support and understood better by students.